2016
DOI: 10.1111/nyas.13099
|View full text |Cite
|
Sign up to set email alerts
|

Mustard vesicating agent–induced toxicity in the skin tissue and silibinin as a potential countermeasure

Abstract: Exposure to the vesicating agents sulfur mustard (SM) and nitrogen mustard (NM) causes severe skin injury with delayed blistering. Depending upon the dose and time of their exposure, edema and erythema develop into blisters, ulceration, necrosis, desquamation, and pigmentation changes, which persist weeks and even years after exposure. Research advances have generated data that have started to explain the probable mechanism of action of vesicant-induced skin toxicity; however, despite these advances, effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…EVRs are reported to occur in up to 6% of patients receiving intravenous cancer chemotherapy ( Bertelli, 1995 , Cassagnol and McBride, 2009 ). Indeed, HN2 exhibits a very complex mechanism of toxicity that involves many macromolecules and cell signaling pathways ( Korkmaz et al, 2006 , McManus and Huebner, 2005 , Tewari-Singh and Agarwal, 2016 ). Our group previously reported that HN2 triggers numerous responses in cultured skin cells in vitro , including damaged nuclear DNA, increased lipid peroxidation and apoptosis via activation of caspases 3 and 9 ( Lulla et al, 2013 , Pino and Billack, 2008 , Pino et al, 2014 ), and that the organoselenium compound ebselen (EB-1) reduces the toxicity of both HN2 ( Hardej and Billack, 2007 , Lulla et al, 2014 ) and the sulfur half mustard CEES in vitro ( Pino et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…EVRs are reported to occur in up to 6% of patients receiving intravenous cancer chemotherapy ( Bertelli, 1995 , Cassagnol and McBride, 2009 ). Indeed, HN2 exhibits a very complex mechanism of toxicity that involves many macromolecules and cell signaling pathways ( Korkmaz et al, 2006 , McManus and Huebner, 2005 , Tewari-Singh and Agarwal, 2016 ). Our group previously reported that HN2 triggers numerous responses in cultured skin cells in vitro , including damaged nuclear DNA, increased lipid peroxidation and apoptosis via activation of caspases 3 and 9 ( Lulla et al, 2013 , Pino and Billack, 2008 , Pino et al, 2014 ), and that the organoselenium compound ebselen (EB-1) reduces the toxicity of both HN2 ( Hardej and Billack, 2007 , Lulla et al, 2014 ) and the sulfur half mustard CEES in vitro ( Pino et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are no effective approved antidotes available for SM. Although a number of compounds including anti-oxidants, protease inhibitors, PARP inhibitors, angiogenesis inhibitors, calcium modulators, anti-inflammatory agents, and flavanones have been shown to be effective to various extents in laboratory studies (Balszuweit et al, 2013; Goswami et al, 2016a; Kadar et al, 2014; Kadar et al, 2009; Laskin et al, 2010; McElroy and Day, 2016; Paromov et al, 2007; Smith, 2009; Tewari-Singh and Agarwal, 2016; Weinberger et al, 2016). There is no specific antidote available against CX-induced injuries and the treatment is mostly supportive to reduce symptoms, prevent infections and help healing.…”
Section: Treatmentmentioning
confidence: 99%
“…2 Nitrogen mustards are specific by their potent alkylating effects 3 and they interact with a number of biomolecules and a characteristic manifestation of poisoning is severe blister formation. 4 These are controlled substances, however, the synthetic pathways are quite simple, precursors are available, and nitrogen mustards therefore still pose an actual threat. The hydrolysis degradation products are ethyl diethanolamine (EDEA), methyl diethanolamine (MDEA), and triethanolamine (TEA).…”
Section: Introductionmentioning
confidence: 99%